2019
DOI: 10.3390/jcm8122158
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolic Events in Patients with Osteonecrosis of the Femoral Head Undergoing Primary Hip Arthroplasty

Abstract: Previous data have shown patients with osteonecrosis of the femoral head (ONFH) have increased lifelong risk of unprovoked venous thromboembolic events (VTE) as compared with the general population, according to sharing common pathological mechanism of endothelial dysfunction. However, whether the risk of VTE increases in those ONFH patients undergoing major hip replacement surgery remains unclear. This is a retrospective nationwide Asian population-based study. From 1997 to 2013, a total of 12,232 ONFH patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although historically, outcomes in patients undergoing TJR for osteonecrosis are worse than those with osteoarthritis, none of patients in the HIV group with osteonecrosis as the presenting diagnosis developed VTE 37 (Table 4). Furthermore, a large study by Sung et al 38 demonstrated similar VTE rates after THA for patients with and without osteonecrosis of the femoral head, thus this likely is less likely to explain the difference in VTE rate between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Although historically, outcomes in patients undergoing TJR for osteonecrosis are worse than those with osteoarthritis, none of patients in the HIV group with osteonecrosis as the presenting diagnosis developed VTE 37 (Table 4). Furthermore, a large study by Sung et al 38 demonstrated similar VTE rates after THA for patients with and without osteonecrosis of the femoral head, thus this likely is less likely to explain the difference in VTE rate between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that males had a higher ALT concentration resulting in a lower AST/ALT ratio at baseline and after the HFHC diet. Elevated ALT is associated with fatty liver and non-alcoholic fatty liver disease but does not define a specific disease [ 54 ]. The reported upper limit of normal of ALT varies greatly between laboratories and sexes (35–79 U.L −1 for males and 31–55 U.L −1 for females) [ 55 ], and although it is established that healthy males have higher ALT concentrations compared to healthy females [ 56 ], the mechanisms underpinning this differences are unknown [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported upper limit of normal of ALT varies greatly between laboratories and sexes (35–79 U.L −1 for males and 31–55 U.L −1 for females) [ 55 ], and although it is established that healthy males have higher ALT concentrations compared to healthy females [ 56 ], the mechanisms underpinning this differences are unknown [ 57 ]. The two-fold greater ALT concentration in males compared to females in the present study reflects the available epidemiological data [ 54 57 ] but is not elevated to an extent which might suggest signs of NAFLD. We anticipated to see increases in the plasma concentration of both triacylglycerol and fatty acids as markers of lipid overload; however, none of these plasma lipid concentrations increased following the HFHC diet in either sex (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%